ANTIBACTERIAL AND CYTOTOXIC POTENCIES OF STILBENE OLIGOMERS FROM STEM BARKS OF BAOTI (DRYOBALANOPS LANCEOLATA) GROWING IN KENDARI, INDONESIA - I, Sahidin; W, Wahyuni; Malaka, Muh Hajrul; I, Imran (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of the research is to isolate and to identify compounds from stem barks of Dryobalanops lanceolata and to evaluate their activities toward bacteria and cancer cell lines. Methods: Isolation of the compounds worked with chromatography methods including thin-layer chromatography, vacuum liquid chromatography, and radial chromatography. All compound structures were determined based on the spectroscopic evidence including ultraviolet (UV), Infrared, and one-dimension and two-dimension nuclear magnetic resonance spectra and comparison the spectroscopy data with related data from references. The biological properties of compounds are evaluated toward bacteria Escherichia coli ATCC 35219 and Staphylococcus aureus ATCC 25923 and human breast cancer cell lines T-47D as cytotoxic potency. Results: Five stilbene oligomers have been isolated and identified from acetone extract of D. lanceolata stem barks namely balanocarpol (1), e-viniferin (2), a-viniferin (3), vaticanol B (4), and hopeaphenol (5). The inhibition zone value (in mm) of e-viniferin, balanocarpol, a-viniferin, hopeaphenol, and vaticanol B toward E. coli and S. aureus is 11±0.22 and 7±0.17, 9±0.17 and 13±0.12, 8±0.20 and 8±0.16, 6±0.16 and 8±0.11, and 5±0.12 and 4±0.14, respectively. Biological activity of the compounds against breast cancer cell lines T-47D (inhibitory concentration 50% in μM) for e-viniferin, balanocarpol, a-viniferin, hopeaphenol, and vaticanol B is 34.13±0.15, 98.17±0.41, 84.79±0.24, 52.04±0.26, and 119.30±0.54, respectively. Conclusions: e-viniferin is the most active compound toward E. coli and human breast cancer cell lines T-47D. Biological activity against bacteria S. aureus indicated that balanocarpol is the most potential compound.